2016
DOI: 10.1093/cercor/bhw159
|View full text |Cite
|
Sign up to set email alerts
|

Region- and Layer-Specific Activation of the Higher Order Auditory Cortex Te2 after Remote Retrieval of Fear or Appetitive Memories

Abstract: The auditory cortex is involved in encoding sounds which have acquired an emotional-motivational charge. However, the neural circuitry engaged by emotional memory processes in the auditory cortex is poorly understood. In this study, we investigated the layers and regions that are recruited in the higher order auditory cortex Te2 by a tone previously paired to either fear or appetitive stimuli in rats. By tracking the protein coded by the immediate early gene zif268, we found that fear memory retrieval engages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…Also coinciding animal findings, this CS-specific odor retuning arose only on Day 9, indicating a time-dependent process likely involved in the transformation of associative learning into long-term memory (Weinberger, 2004). Moreover, the site of this retuning-the PPC, a secondary olfactory cortex-conformed to animal findings, emphasizing conditioning-induced plasticity and long-term memory storage in the secondary sensory cortex (relative to primary or higher sensory levels; Diamond and Weinberger, 1984;Grosso et al, 2015bGrosso et al, , 2017Holschneider et al, 2006;Poremba et al, 1998). The timing (Day 9 only) and site (PPC only) of tuning shifts paralleled changes in higher-order, spatially distributed neuronal ensemble responses in the PPC (i.e., biased PPC classification to the threat CS on Day 9).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Also coinciding animal findings, this CS-specific odor retuning arose only on Day 9, indicating a time-dependent process likely involved in the transformation of associative learning into long-term memory (Weinberger, 2004). Moreover, the site of this retuning-the PPC, a secondary olfactory cortex-conformed to animal findings, emphasizing conditioning-induced plasticity and long-term memory storage in the secondary sensory cortex (relative to primary or higher sensory levels; Diamond and Weinberger, 1984;Grosso et al, 2015bGrosso et al, , 2017Holschneider et al, 2006;Poremba et al, 1998). The timing (Day 9 only) and site (PPC only) of tuning shifts paralleled changes in higher-order, spatially distributed neuronal ensemble responses in the PPC (i.e., biased PPC classification to the threat CS on Day 9).…”
Section: Discussionsupporting
confidence: 80%
“…Animal evidence further suggests that this associative plasticity in the sensory cortex not only emerges immediately after conditioning but also shows long-term retention with growing specificity to the CS (Weinberger, 2004). Importantly, associative plasticity in the secondary sensory cortex, both immediate and long-lasting, plays a critical role in threat memory, with the immediate plasticity being necessary for the formation (Cambiaghi et al, 2016a;Grosso et al, 2015b;Yang et al, 2016) and the lasting plasticity necessary for the long-term storage (Cambiaghi et al, 2016b;Grosso et al, 2015bGrosso et al, , 2017Kwon et al, 2012;Sacco and Sacchetti, 2010) of threat memory.…”
Section: Introductionmentioning
confidence: 98%
“…To better address this issue, we employed an alternative method based on the expression of the immediate early gene zif268. Immediate early genes are required for synaptic plasticity and are used as an index of neuronal activation (Frankland and Bontempi, 2005; Sacco and Sacchetti, 2010; Lesburguères et al, 2011; Kwon et al, 2012; Grosso et al, 2017). Among immediate-early genes, zif268 expression has been associated with long-term plasticity that occurs during memory retrieval (Frankland et al, 2004; Kwon et al, 2012; Xie et al, 2014; Grosso et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Immediate early genes are required for synaptic plasticity and are used as an index of neuronal activation (Frankland and Bontempi, 2005; Sacco and Sacchetti, 2010; Lesburguères et al, 2011; Kwon et al, 2012; Grosso et al, 2017). Among immediate-early genes, zif268 expression has been associated with long-term plasticity that occurs during memory retrieval (Frankland et al, 2004; Kwon et al, 2012; Xie et al, 2014; Grosso et al, 2017). Accordingly, several recent studies have shown changes in zif268 expression in the sensory cortex following emotional memory recall (Hall et al, 2001; Maviel et al, 2004; Sacco and Sacchetti, 2010; Kwon et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation